Characteristics of soil aggregate distribution and organic carbon mineralization in quinoa fields with different soil textures in the northern of the Yinshan Mountains in inner Mongolia - Lv, Shuning; Liu, Ruixiang; Guo, Zhanbin; Wang, Shuyan (Frontiers in Environmental Science, 2024)
The sub-mountain plains area at the northern foothills of the Yinshan Mountains in Inner Mongolia is an important grain producing area in the cold and arid regions of China, but due to climatic and environmental factors, it has resulted in a fragile ecological environment, degradation of arable land, and serious soil erosion. Quinoa (Chenopodium quinoa Willd.) is a hardy, cold and saline tolerant crop with much higher protein content than other crops. Therefore, it has begun to be grown on a large scale in the region in recent years. In order to investigate the distribution characteristics of soil aggregates and organic carbon (SOC) in quinoa fields in ecologically fragile areas, four quinoa fields with different soil textures, namely, sandy soil, sandy loam, loamy soil and clay loam, were selected for this experiment, and the mass percentages of different soil aggregate particle sizes and the organic carbon content of each particle size were determined before and after quinoa planting, and the organic carbon mineralisation in soil aggregates of quinoa fields with different textures was analysed through indoor organic carbon mineralisation cultures. The dynamic characteristics were analysed. The results showed that the stability of soil aggregates was enhanced after planting quinoa, and the highest mass percentage of aggregates with >2 mm particle size was 27.95% in clay loam soil. Planting quinoa in loamy soil had the most obvious effect on promoting the formation of soil macroaggregates, while the organic carbon content increased the most. The organic carbon (SOC) content of soil aggregates of all grain sizes increased by 0.45–3.09 g kg-1 compared to the pre-sowing period, with the fastest rate and greatest intensity of organic carbon mineralisation in aggregates of 2–0.25 mm grain size. The study showed that growing quinoa in loamy soils improves soil structure, slows down the rate of soil organic carbon mineralization, and increases soil carbon sequestration capacity.